2020
DOI: 10.1093/nar/gkaa657
|View full text |Cite
|
Sign up to set email alerts
|

On the expanding roles of tRNA fragments in modulating cell behavior

Abstract: The fragments that derive from transfer RNAs (tRNAs) are an emerging category of regulatory RNAs. Known as tRFs, these fragments were reported for the first time only a decade ago, making them a relatively recent addition to the ever-expanding pantheon of non-coding RNAs. tRFs are short, 16–35 nucleotides (nts) in length, and produced through cleavage of mature and precursor tRNAs at various positions. Both cleavage positions and relative tRF abundance depend strongly on context, including the tissue type, tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
134
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(151 citation statements)
references
References 150 publications
(231 reference statements)
0
134
1
Order By: Relevance
“…Among tRNA roles outside ribosomal protein synthesis, the following have been previously highlighted: nutrient sensing, transcription regulation, retroelement insertion, translation kinetics and protein folding, stress response, immune response, apoptosis inhibition, peptidic antibiotic biosynthesis, bacterial wall biosynthesis, post-translational protein modification, membrane lipid modification, retroviral replication, mitochondrial ribosome assembly, and mitochondrial DNA replication ( Seligmann, 2010 ; Raina and Ibba, 2014 ; Katz et al, 2016 ; Balasubramaniam et al, 2017 ; Bogenhagen et al, 2018 ; Su et al, 2020 ; and this issue). Also, several roles have been described for tRNA fragments, among which the following stand out: gene silencing, translation regulation, transposable element regulation, noncoding RNA regulation, cell differentiation, cell proliferation and cancer, host defense, stress response, apoptosis, and epigenetic inheritance ( Magee and Rigoutsos, 2020 ; Polacek and Ivanov, 2020 ; Su et al, 2020 ; and this issue). In most cases, the information about the precise isotype, state of post-transcriptional modification, recognition by the cognate aminoacyl-tRNA synthetase, and aminoacylation state is still scarce, leaving the door open for new research avenues.…”
Section: Possible Clues For the Absence Of Trna Genesmentioning
confidence: 99%
“…Among tRNA roles outside ribosomal protein synthesis, the following have been previously highlighted: nutrient sensing, transcription regulation, retroelement insertion, translation kinetics and protein folding, stress response, immune response, apoptosis inhibition, peptidic antibiotic biosynthesis, bacterial wall biosynthesis, post-translational protein modification, membrane lipid modification, retroviral replication, mitochondrial ribosome assembly, and mitochondrial DNA replication ( Seligmann, 2010 ; Raina and Ibba, 2014 ; Katz et al, 2016 ; Balasubramaniam et al, 2017 ; Bogenhagen et al, 2018 ; Su et al, 2020 ; and this issue). Also, several roles have been described for tRNA fragments, among which the following stand out: gene silencing, translation regulation, transposable element regulation, noncoding RNA regulation, cell differentiation, cell proliferation and cancer, host defense, stress response, apoptosis, and epigenetic inheritance ( Magee and Rigoutsos, 2020 ; Polacek and Ivanov, 2020 ; Su et al, 2020 ; and this issue). In most cases, the information about the precise isotype, state of post-transcriptional modification, recognition by the cognate aminoacyl-tRNA synthetase, and aminoacylation state is still scarce, leaving the door open for new research avenues.…”
Section: Possible Clues For the Absence Of Trna Genesmentioning
confidence: 99%
“…Although the function of tRNAs as adapter molecules is well known, recent studies have shown that they are a major source of small noncoding RNAs that, together with other small RNAs such as PIWI-interacting RNAs (piRNAs), ribosomal-derived small RNAs, small nucleolar RNAs (snRNAs), and microRNAs (miRNAs), play an active role in diverse biological processes such as RNA processing, post-transcriptional and post-translational regulation, cell proliferation and apoptosis, vesicle-mediated intercellular communication, and intergenerational inheritance [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Small RNAs derived from tRNAs are generated by enzymatic cleavage of the parental (precursor and mature) tRNAs [19,35,36,39,43] ( Figure 1). A large variety of tRNA fragments exists which have been classified into seven groups based on their position within the parental tRNA sequence: 5 or 3 small tRNA fragments (tRFs) of ≤30 nucleotides that are generated from the 5 or 3 ends of the parental mature tRNA, internal tRNA fragments (i-tRFs) of varying lengths (16 to 33 nucleotides), 5 or 3 33 nucleotide-long tRNA halves (tRHs) and 5 U-tRFs and tRF-1s derived from precursor tRNAs and containing part of the 5 leader or 3 trailer sequence, respectively [35] ( Figure 1).…”
Section: Trna Fragments a New Class Of Small Noncoding Rnasmentioning
confidence: 99%
“…Small RNAs derived from tRNAs are generated by enzymatic cleavage of the parental (precursor and mature) tRNAs [19,35,36,39,43] ( Figure 1). A large variety of tRNA fragments exists which have been classified into seven groups based on their position within the parental tRNA sequence: 5 or 3 small tRNA fragments (tRFs) of ≤30 nucleotides that are generated from the 5 or 3 ends of the parental mature tRNA, internal tRNA fragments (i-tRFs) of varying lengths (16 to 33 nucleotides), 5 or 3 33 nucleotide-long tRNA halves (tRHs) and 5 U-tRFs and tRF-1s derived from precursor tRNAs and containing part of the 5 leader or 3 trailer sequence, respectively [35] ( Figure 1). The endonucleases Angiogenin, RNAse T2, Dicer, and RNaseZ/ELAC2 generate some but not all tRNA fragments [27,[44][45][46], suggesting that other tRNA cleaving enzymes remain to be identified [47].…”
Section: Trna Fragments a New Class Of Small Noncoding Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…The exploration of miRNA expression profiles has added valuable insights into mechanisms of cell processes in health and disease (2,9). tRNA fragments and halves (tRFs) have more recently become of interest through their role in pathophysiology (10). They are thought to increase based on cell stressors and have variable expression patterns based on cell type and method of cell stress (11).…”
Section: Introductionmentioning
confidence: 99%